2004
DOI: 10.1124/mol.104.005553
|View full text |Cite
|
Sign up to set email alerts
|

Ertiprotafib Improves Glycemic Control and Lowers Lipids via Multiple Mechanisms

Abstract: Ertiprotafib belongs to a novel class of insulin sensitizers developed for treatment of type 2 diabetes. In insulin-resistant rodent models, ertiprotafib and a close analog lowered both fasting blood glucose and insulin levels and improved glycemic excursion during an oral glucose tolerance test. In addition, treatment of rodents improved lipid profiles, with significantly lowered triglyceride and free fatty acid levels. These results suggested that this therapeutic activity might involve mechanisms in additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 42 publications
2
53
1
Order By: Relevance
“…In the light of this complexity of multiple mechanisms, which could complicate its preclinical efficacy and potentially contribute to its side effects, it was discontinued in Phase II clinical trials. 134 136 Vanadate and pervanadate (the complexes of vanadate with hydrogen peroxide) are two commonly used general PTP inhibitors. These compounds also have insulin-mimetic properties, an observation that has generated a great deal of interest.…”
Section: E Benzofuran and Benzothiophene Biphenylsmentioning
confidence: 99%
“…In the light of this complexity of multiple mechanisms, which could complicate its preclinical efficacy and potentially contribute to its side effects, it was discontinued in Phase II clinical trials. 134 136 Vanadate and pervanadate (the complexes of vanadate with hydrogen peroxide) are two commonly used general PTP inhibitors. These compounds also have insulin-mimetic properties, an observation that has generated a great deal of interest.…”
Section: E Benzofuran and Benzothiophene Biphenylsmentioning
confidence: 99%
“…Ertiprotafib (Wyeth Pharmaceuticals; acquired by Pfizer) showed initial promise by lowering blood glucose levels when orally administered to mice 48 and progressed to a phase II clinical trial. Further studies also indicated decreased insulin levels, along with lowered triglyceride and free fatty acid levels; however, these outcomes were reported to be likely due to off-target effects of ertiprotafib, which include activation of peroxisome proliferator-activated receptor α (PPARα) and PPARγ 49 , and potent inhibition of IκB kinase β (IKK-β) 50 . Phase II trials with ertiprotafib were discontinued, likely due to its lack of in vivo efficacy, coupled with unwanted side effects 49 .…”
Section: Strategies To Modulate Liver Glucose and Glycogen Metabolismmentioning
confidence: 99%
“…Yield = 42%, mp 233.1-234.3 °C; (17). Yield = 55%, mp 99.7-103.3 °C; (18). Yield = 47%, mp 102.8-107.4 °C; (19).…”
Section: General Procedures For the Preparation Of Derivatives 9-19mentioning
confidence: 99%
“…A variety of PTP1B inhibitors have been disclosed among academic and industrial laboratories [15][16][17]. Two compounds, ertiprotafib and trodusquemine, have progressed to clinical trials [18,19]. However, ertiprotafib was discontinued in phase II clinical trials due to a lack of efficacy and side effects [20].…”
Section: Introductionmentioning
confidence: 99%